2005
DOI: 10.1051/agro:2005004
|View full text |Cite
|
Sign up to set email alerts
|

Microalgae community structure analysis based on 18S rDNA amplification from DNA extracted directly from soil as a potential soil bioindicator

Abstract: Soil algae are photosynthetically active microorganisms showing changeable community structure, depending on the soil type, the agricultural practices and the application of pesticides. To characterise algal community structure, molecular approaches complementary to classical microbiological approaches based on the isolation and the culture of soil algae are required. Our study describes a polymerase chain reaction (PCR) approach targeting algal 18S rDNA sequences of desoxyribonucleic acid (DNA) samples extrac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(25 citation statements)
references
References 44 publications
0
25
0
Order By: Relevance
“…The 18S rRNA genes were amplified using the primer pairs P73 (5'-AAT CAG TTA TAG TTT ATT TGR TGG TAC C-3') and P47 (5'-TCT CAG GCT CCC TCT CCG GA-3') (Berard et al 2005) and EukA (5'-AAC CTG GTT GAT CCT GCC AGT-3') and EukB (5'-TGA TCC TTC TGC AGG TTC ACC TAC-3') (dieZ et al 2001). PCRs were carried out in 25 µl aliquots containing approximately 100 ng DNA, a deoxynucleoside triphosphate mixture (0.2 mM each), buffer (1/10 volume of the supplied 10x buffer) supplemented to give a final concentration of 3 mM MgCl 2 , 1 U of Taq polymerase (Promega), and 0.5 pmol of each primer.…”
Section: Methodsmentioning
confidence: 99%
“…The 18S rRNA genes were amplified using the primer pairs P73 (5'-AAT CAG TTA TAG TTT ATT TGR TGG TAC C-3') and P47 (5'-TCT CAG GCT CCC TCT CCG GA-3') (Berard et al 2005) and EukA (5'-AAC CTG GTT GAT CCT GCC AGT-3') and EukB (5'-TGA TCC TTC TGC AGG TTC ACC TAC-3') (dieZ et al 2001). PCRs were carried out in 25 µl aliquots containing approximately 100 ng DNA, a deoxynucleoside triphosphate mixture (0.2 mM each), buffer (1/10 volume of the supplied 10x buffer) supplemented to give a final concentration of 3 mM MgCl 2 , 1 U of Taq polymerase (Promega), and 0.5 pmol of each primer.…”
Section: Methodsmentioning
confidence: 99%
“…Due to their metabolic pathway close to higher plants, microalgae and cyanobacteria are major targets of herbicides molecules compared to the often studied bacteria and fungi, in microbial ecotoxicology studies. Acquisition of knowledge on the diversity and the functioning of soil phototrophic communities and their responses to herbicides contaminations represents therefor a major issue in order to identify good pollution indicators in soil (Bérard et al , 2005Zancan et al 2006). In this purpose, the analysis of pigment composition to characterize phototrophic microbial structure is already a recognized tool to study this specific community in comparison with microscopic and culture methods (Dorigo et al 2004;Kirkwood and Henley 2006).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the lysis of Bacillariophyceae cells is difficult, hampering DNA extraction, probably because of the presence of the robust silicate valves (Bérard et al. ). In this study, our data set showed that DGGE diversity was more closely related to generic diversity, but it did not enable us to unequivocally determine whether diversity with lower resolution power at the species level could also be reliable.…”
Section: Resultsmentioning
confidence: 99%